KEANEKARAGAMAN TUMBUHAN PEKARANGAN DI LINGKUNGAN TURIDA BARAT, KELURAHAN TURIDA, KECAMATAN SANDUBAYA, KOTA MATARAM - Elsa Fitriani; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Turida Hamlet located in Turida Barat, Sandubaya District, Mataram City, West Nusa Tenggara has potential diversity of homegarden plants. This study aims to analyze the level of species diversity of homegarden plants in the area. The method used was direct observation of plants found in community homegardens. The collected data were analyzed using the Shannon-Wiener diversity index (H’). The results showed that there were 15 plant species with varying number of individuals. The diversity index (H’) value obtained was 2.55, which is categorized as moderate diversity. In addition, the evenness index (E) value of 0.76 indicates that the distribution of individuals among species is relatively even and there is no significant dominance by certain species. Therefore, the homegarden plant community in Turida Hamlet has moderate diversity with relatively stable ecosystem conditions.